ANALISIS CUSTOMER RELATIONSHIP MANAGEMENT DAN SERVICE QUALITY TERHADAP CUSTOMER VALUE MELALUI CUSTOMER SATISFACTION PADA BANK PEMERINTAH DI SURABAYA - Kusnadi, A.M. (Program Doktor Ilmu Ekonomi, 2010)
The aim of this study was to know and analyze : (1) Influence of customer relationship management on Customer Satisfaction, (2) Influence of customer management on Customer Value , (3) Influence of service quality on Customer Satisfaction , (4) Influence of service quality on customer value, (5) Influence of Customer Satisfaction on Customer Value , (6) Influences of customer relationship management and service quality on Customer Value through Customer Satisfaction, (7) Influence of customer relationship management on Customer Value through Customer Satisfaction , (8) Influence of service quality on customer value through customer satisfaction, (9) Influence of service quality on customer relationship management . The population in this study involved all customers of current account, saving, and time deposit in Surabaya, with minimum criteria of 3 (three) months being customers. Accidental sampling technique was used in this research and 400 customers were obtained. Structural equation modeling (SEM) was used as analysis technique by using AMOS 4.01 software. The result of this study showed that customer analysis management and service quality provided significant influences on customer value through Customer Satisfaction in state banks in Surabaya Keywords: Customer relationship management, service quality, Customer Satisfaction , value.